DNA copy number variants: A potentially useful predictor of early onset renal failure in boys with posterior urethral valves. Issue 4 (August 2016) - Faure, A.; Bouty, A.; Caruana, G.; Williams, L.; Burgess, T.; Wong, M.N.; James, P.A.; O'Brien, M.; Walker, A.; Bertram, J.F.; Heloury, Y.
Summary: Introduction: Posterior urethral valves (PUV) are among the most common urological causes of chronic kidney disease (CKD) in childhood. Recently, genomic imbalances have been cited as potential risk factors for altered kidney function and have been associated with CKD. The phenotypic effects of a copy number variant (CNV) in boys with PUV are unknown. Here, it was hypothesised that the progression to early renal failure in PUV patients may be influenced by genetic aberrations. Objective: To assess the relationship between CNVs and renal outcomes. Patients and methods: Between September 2012 and July 2015, 45 children with PUV were recruited to evaluate the presence of CNVs in their DNA. The patients' medical records were retrospectively reviewed. The criteria for outcomes of renal function included: assessments of the nadir serum creatinine in the first year of life, the estimated glomerular filtration rate at 1 and 5 years, and the requirement for renal replacement. Results: Thirteen CNVs were identified in 12 boys (29% of the cohort). Microarray analysis revealed two pathogenic CNVs (well-established CNVs known to be associated with genetic disease) and 11 of unknown significance (CNVs with insufficient current available evidence for unequivocal determination of clinical significance), including genes that have been previously implicated in kidney diseases and urogenital disorders. The median follow-up was 10.2 years (range 3–17.5) in the group of patients with CNV compared with 5.8 years (range 1–16.6) in those CNV−. The nadir creatinine values were significantly higher in boys with CNVs than in those without CNVs (57.5 μmol/L (range 23–215) and 28 μmol/L (range 18–155), respectively ( P  = 0.05) (Figure). Boys CNV+ had a worse prognosis, with a higher incidence of Stage-V CKD compared with the control group (33% with CNVs vs. 9% in CNV−, P  = 0.06) at a median age of 22 months (range 8 months–16 years). Four (33%) patients CNV+ underwent renal transplantation. Discussion: The role of CNVs in the deterioration of renal function remains unknown. It can be hypothesised that CNVs could be a contributing factor or may serve as an accelerant for the progression to renal failure. Conclusion: The CNVs >100 Kb were significantly associated with early onset renal failure in children with PUV. Prenatal detection of CNV could help to identify foetuses at high risk of severe renal impairment in cases of suspected PUV, especially in cases without oligohydramnios or severe pulmonary hypoplasia. These preliminary results should be confirmed in a larger cohort of patients. Summary Figure Box plot graphic representation of nadir of creatinine value during the first year of life according to the presence of CNV (CNV+) or the absence of CNV (CNV−).